NITROGEN POTENTIAL DURING ION NITRIDING PROCESS IN GLOW-DISCHARGE PLASMA - A. A. Kozlov (Наука и техника)
The paper considers problems on regulation of phase composition of a nitrided layer during gas and ion nitriding process in a glow-discharge. It has been established that  available models for control of nitrided layer structure with the help of nitriding index (nitrogen potential) can not be applied for nitriding process in the glow-discharge. Principal difference of the ion nitriding from the gas one is in the fact that chemically active nitrogen is formed in the discharge zone (cathode layer) and its mass-transfer is carried out in the form of an active particle flow (ions, atoms, molecules) which directed to the metal surface.Interrelation of chemical discharge activity with such characteristics of nitriding steel as nitrogen solubility in  α-solid solution and  coefficient diffusion during ion nitriding in low-discharge plasma. It has been shown that regulation of the nitride layer structure during ion nitriding is reached due to changes in nitrogen flow density in plasma. While supporting the flow at the level of nitrogen solubility in  one phase or another (α, γ′)  it is possible to obtain the nitrided layer consisting only of α-solid solution or γ′-nitride layer and diffusion sub-layer. Moreover a specific range of nitrogen flow density values exists for every steel grade where it is possible to ensure a limiting nitrogen concentration in α-solid solution and the γ′-layer characterized by low diffusion  mobility is not formed on the surface.